A Tug of War: Pursuing Justice Amid Armed Conflict. Issue 2 (3rd April 2022) - Drange, Bård
ABSTRACT: Despite its prevalence in armed conflicts globally, the pursuit of justice and human rights during armed conflict has received relatively little attention compared with efforts taken post-conflict. In this article, I discuss the trajectory of state-led measures to tackle human rights abuses while violence is ongoing, with a focus on the interplay between actors seeking to expose and those seeking to conceal human rights abuses. This expose–conceal framework is used to study the search for justice for abuses committed by paramilitary groups in Colombia in the 2000s. I argue that various domestic and international human rights advocates and civil society organisations clashed with the Colombian Government over questions of accountability. Persistent efforts to expose or conceal abuses produced a tug-of-war dynamic, where the two sides pulled the political debate and judicial frameworks in their preferred direction. This article contributes a conflict studies perspective on the establishment of national-level institutions to advance human rights in a context of high impunity and amid armed conflict. Going forward, I argue that more attention to the during-conflict period can enhance our understanding of how the pursuit of justice plays out after conflict.